Catasetum × sheyllae (Orchidaceae: Catasetinae), a new natural hybrid from Brazilian Amazon - Cantuária, Patrick De Castro; Krahl, Dayse Raiane Passos; Krahl, Amauri Herbert; Chiron, Guy; Da Silva, João Batista Fernandes (Phytotaxa, 2021)
Natural hybridization has often been recorded within certain genera of orchids, one of them is Catasetum. During a field study in a forest de igapó in Brazilian Amazon, a new natural hybrid was found, it is here described as Catasetum × sheyllae. Its morphological features, mainly the structures of the lip, are intermediate between those of its putative parent species, C. boyi and C. garnettianum, both observed in sympatry.